Coordinated and High-Level Expression of Biosynthetic Pathway Genes Is Responsible for the Production of a Major Floral Scent Compound Methyl Benzoate in Hedychium coronarium - Yue, Yuechong; Wang, Lan; Yu, Rangcai; Chen, Feng; He, Jieling; Li, Xinyue; Yu, Yunyi; Fan, Yanping (Frontiers in Plant Science, 2021)
Methyl benzoate is a constituent of floral scent profile of many flowering plants. However, its biosynthesis, particularly in monocots, is scarcely reported. The monocot Hedychium coronarium is a popular ornamental plant in tropical and subtropical regions partly for its intense and inviting fragrance, which is mainly determined by methyl benzoate and monoterpenes. Interestingly, several related Hedychium species lack floral scent. Here, we studied the molecular mechanism of methyl benzoate biosynthesis in H. coronarium. The emission of methyl benzoate in H. coronarium was found to be flower-specific and developmentally regulated. As such, seven candidate genes associated with methyl benzoate biosynthesis were identified from flower transcriptome of H. coronarium and isolated. Among them, HcBSMT1 and HcBSMT2 were demonstrated to catalyze the methylation of benzoic acid and salicylic acid to form methyl benzoate and methyl salicylate, respectively. Methyl salicylate is a minor constituent of H. coronarium floral scent. Kinetic analysis revealed that HcBSMT2 exhibits a 16.6-fold lower Km value for benzoic acid than HcBSMT1, indicating its dominant role for floral methyl benzoate formation. The seven genes associated with methyl benzoate biosynthesis exhibited flower-specific or flower-preferential expression that was developmentally regulated. The gene expression and correlation analysis suggests that HcCNL and HcBSMT2 play critical roles in the regulation of methyl benzoate biosynthesis. Comparison of emission and gene expression among four Hedychium species suggested that coordinated and high-level expression of biosynthetic pathway genes is responsible for the massive emission of floral methyl benzoate in H. coronarium. Our results provide new insights into the molecular mechanism for methyl benzoate biosynthesis in monocots and identify useful molecular targets for genetic modification of scent-related traits in Hedychium.